The effect of cobalt on morphology, structure, and ORR activity of electrospun carbon fibre mats in aqueous alkaline environments - Gehring, Markus; Kutsch, Tobias; Camara, Osmane; Merlen, Alexandre; Tempel, Hermann; Kungl, Hans; Eichel, Rüdiger-A. (Beilstein Journal of Nanotechnology, 2021)
An innovative approach for the design of air electrodes for metal–air batteries are free-standing scaffolds made of electrospun polyacrylonitrile fibres. In this study, cobalt-decorated fibres are prepared, and the influence of carbonisation temperature on the resulting particle decoration, as well as on fibre structure and morphology is discussed. Scanning electron microscopy, Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, elemental analysis, and inductively coupled plasma optical emission spectrometry are used for characterisation. The modified fibre system is compared to a benchmark system without cobalt additives. Cobalt is known to catalyse the formation of graphite in carbonaceous materials at elevated temperatures. As a result of cobalt migration in the material the resulting overall morphology is that of turbostratic carbon. Nitrogen removal and nitrogen-type distribution are enhanced by the cobalt additives. At lower carbonisation temperatures cobalt is distributed over the surface of the fibres, whereas at high carbonisation temperatures it forms particles with diameters up to 300 nm. Free-standing, current-collector-free electrodes assembled from carbonised cobalt-decorated fibre mats display promising performance for the oxygen reduction reaction in aqueous alkaline media. High current densities at an overpotential of 100 mV and low overpotentials at current densities of 333 μA·cm−2 were found for all electrodes made from cobalt-decorated fibre mats carbonised at temperatures between 800 and 1000 °C.
Keywords: carbon fibres; cobalt-decorated fibres; electrospinning; metal–air batteries; oxygen reduction